A comparative evaluation of penetration depth and surface microhardness of Resin Infiltrant, CPP-ACPF and Novamin on enamel demineralization after banding: an in vitro study. Issue 1 (1st January 2021) - Rana, Nishita; Singh, Namita; Shaila,; Thomas, Abi. M.; Jairath, Rajan
Abstract: Background: The field of dentistry has been revolutionized by various concepts. Minimal invasive dentistry is the preferred treatment approach in the present era; therefore, various techniques have been advocated to arrest caries lesions at an early stage on the grounds of better understanding of the dynamic nature of dental caries. Thus, study was conducted to compare and evaluate the penetration depth and enamel microhardness of Resin Infiltrant, CPP-ACPF and Novamin on artificial demineralized enamel surface after orthodontic banding. Material and methods: Eighty extracted sound premolars were banded. The bands were cemented with type 1 GIC and further divided into – Group I: Resin Infiltrant, Group II: CCP-ACPF, Group III: Novamin and Group IV: Control. The samples were incubated for 30 days and then thermocycled. A window of 4 mm × 4 mm was prepared on the buccal surface of samples and artificially demineralized for 4 weeks. A single application was made for Resin Infiltrant, while Novamin and CCP-ACPF were applied twice daily. These samples were otherwise immersed in artificial saliva, and this was protocol was observed for 14 days. For the evaluation of penetration depth, 10 samples from each group were bucco-lingually sectioned and immersed in methylene blue dye solution for 24 h and then evaluated under stereomicroscope. For the enamel surface microhardness, remaining 10 samples from each group were embedded in acrylic resin with outer buccal surface exposed and were tested by a using digital Micro-Vickers hardness tester. Results: All groups showed a significant difference in the depth of dye penetration and surface microhardness compared to the control group. As compared to the other tested groups, Resin Infiltrant exhibited the highest significant reduction in demineralization and increased microhardness. Novamin had a deeper penetration and increase in microhardness as compared to CCP-ACPF. Conclusion: Resin Infiltrant exhibited the highest potential to impede caries and constitutes a competent aerosol free micro-invasive strategy for combating non cavitated lesions approaching the outer layer dentine which are too advanced for remineralizing agents but do not necessarily require any drilling of tooth.